Rhythmic abdominal pumping movements in praying Mantises (Insecta: Mantodea) - Prete, Frederick R.; Schirmer, Aaron E.; Patel, Salim; Carrion, Christina; Prete, Greg M.; van Alphen, Bart; Svenson, Gavin J. (Fragmenta entomologica, 2019)
We analyzed the rhythmic, cyclical dorsal-ventral abdominal pumping movements of nymphal and adult Hierodula patellifera (Audinet- Serville 1839), and adult Stagmomantis carolina (Johansson 1763), Tenodera sinensis (de Saussure 1871), Miomantis paykullii (Stål 1871), and Sphodromantis lineola (Burmeister 1838) using a combination of customized video analysis software and frame-by-frame video analyses. Despite the phylogenetic and ecological diversity of these species, we found fundamental similarities in the overall, intermittent patterns of their abdominal pumping movements. In adults of all species, intermittent bouts of abdominal pumping had median durations of 64-89 sec, and were separated by intervals with median durations of 10-25 sec. Bouts began with rhythmic upward abdominal deflections of progressively increasing amplitude and frequency which were superimposed on an overall, progressive abdominal elevation. Bouts ended with 1-4 very high amplitude, low frequency upward deflections after which the abdomen returned to its horizontal (resting) position. In H. patellifera, the overall adult pattern emerged gradually during larval development. Given the diversity of the species tested, our data suggest that intermittent abdominal pumping (which has been associated with respiratory behavior in insects) may be independent of ecological niche or acute environmental stressors in mantises. Instead, our data support the hypothesis that these apparently respiratory related, intermittent abdominal pumping movements are an emergent property of the mantis central nervous system organization.